ANALISIS MANAJEMEN KAS, MANAJEMEN PIUTANG, DAN MANAJEMEN PERSEDIAAN DALAM MENINGKATKAN RENTABILITAS EKONOMI PADA CV PRIMA MOTOR PASIR PENGARAIAN, RIAU PERIODE 2013 - 2017 - May Syadtri; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determinine cash management, receivable management and inventory management in increasing economic profitability at Cv Prima Motor, Pasir Pengaraian, Riau for the Period 2013-2017. The subjects in this study were CV Prima Motor and the 2013-2017 financial statement research object which included items in the balance sheet and income statement. The data collection method used in this study is documentation. The data analysis method used in this study is financial ratio analysis. Based on the results of the study note that cash management (cash turnover) is categorized as good because it is above the industry standard 10 times. Management of accounts receivable (accounts receivable turnover) is categorized as good because it is above the industry standard 15 times. Inventory management (inventory turnover) is considered bad because it is still below the industry standard. Economic profitability (return on investment) is categorized as not good because it is still below the industry standard. Keywords : Cash Management Receivables Management, Inventory Management , Economic Profitability